IJCM_323A: Assessment of Caregiver Burden Among Family Members of People Living with HIV/AIDS (PLHIV) in Costal Andhra Pradesh, India: - Mixed Method Study - Kumar Pathipaka Sravan; Madhavi B. Devi; Harish K. (Wolters Kluwer Medknow Publications, 2024)
Background: As PLHIV now live longer, family caregivers play a crucial role in providing physical, emotional, and financial support. This study investigates the burden experienced by family caregivers of People Living with AIDS (PLHIV) in Kakinada District, Andhra Pradesh. Objectives: 1. To assess burden Among caregivers (family members) of PLHIV. 2. To Explore care giver perspective of caring experiences Methodology: Methodology: The study is a cross-sectional study. By using mixed-method approach both qualitative and quantitative data was collected by convenient sampling method in an ART Centre of Kakinada District. Prior approval was taken from Institutional Ethics Committee. A pretested semi-structured questionnaire for socio-demographic information and validated, standardized 22-item Zarit Burden Interview (ZBI) tool to assess the perceived caregiver burden. Quantitative analysis done by using SPSS and Qualitative Information gathered through in-depth interviews. These were recorded, transcribed, translated, and later coded for analysis following thematic approach. Results: Demographics revealed that Female were 54.8% and Male were 45.2%. The mean age group was 38.38Â±11.5. In this study revealed that 22.6% were under severe burden & 12.9 % were moderate to severe &38.7% were mild to moderate burden. Mean Zarit Burden score was 36.32Â±18.8. Caregivers faced a range of challenges, pertaining to physical, psychological, emotional, social, and financial burden. Challenges experienced by the them regarding stigma and discrimination are more common. Conclusion: Majority of caregivers having Burden. Caring for someone with HIV/AIDS brings both positive and tough experiences for caregivers. ongoing support is crucial for families in this situation. Simple, focused measures can make a real difference in the well-being for caregivers and Improve Care givers experience.